To set up the equation based on the scenario:
- Let \( b \) be the original bill amount.
- The dessert cost \( L = 12 \).
- The restaurant friend removed the dessert from the bill, so the reduced bill will be \( b - L \) or \( b - 12 \).
- Stan tipped 20% on the reduced bill, and we know the tip amount was \( 15 \).
The equation for the tip would be:
\[ 0.20(b - L) = 15 \]
Substituting \( L = 12 \) into the equation gives:
\[ 0.20(b - 12) = 15 \]
Now, we can fill in the blanks based on this setup:
- \( e = 0.20 \)
- \( b = b \)
- \( L = 12 \)
The equation can be expressed as:
\[ 0.20(b - 12) = 15 \]
So, filling in the blanks in the form \( e - (b - L) = | \) will not be appropriate since that does not represent the original calculation correctly. However, based on the above calculation, the main equation we arrive at should help you solve for \( b \):
\[ 0.20(b - 12) = 15 \]
To find \( b \) from this equation, solve for \( b \):
-
Divide both sides by \( 0.20 \): \[ b - 12 = \frac{15}{0.20} \]
-
Calculate \( \frac{15}{0.20} = 75 \): \[ b - 12 = 75 \]
-
Finally, add \( 12 \) to both sides: \[ b = 75 + 12 = 87 \]
Thus, the original bill was \( 87 \).